Forecasting cocoa yields for 2050 - Kozicka, M.; Tacconi, F.; Horna, D.; Gotor, Elisabetta (2018)
Cocoa is a food-industrial crop that could play a more important role in poverty reduction for small producers in developing countries worldwide. Every year, the cocoa-chocolate value chain moves billions of dollars, providing important dividends for producing countries and for national and international companies around the world. The International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) is a structural simulation model, which allows for future analysis of cocoa market globally. The model has been developed at International Food Policy Research Institute (IFPRI) to consider the long-term challenges facing policymakers in reducing hunger, and poverty in a sustainable fashion. IMPACT is the main quantitative tool used by the Global Futures & Strategic Foresight (GFSF) initiative, in which Bioversity International is involved as a partner. The aim of this study is to validate the performance and improve parameterization of IMPACT cocoa components. The main objective is to review and suggest changes to the Intrinsic Productivity Growth Rates (IPRs) for cocoa in order to improve the model’s baseline projections. It focuses on the ten largest cocoa producing countries in reviewing parameters related to yield growth rates until 2050. Based on historical cocoa yield time series, as reported by FAOStat, forecasts are made using an Autoregressive Integrated Moving Average (ARIMA). The forecasts, together with statistically estimated prediction intervals, supported by literature sources and expert knowledge are compared against respective yield trajectories embedded in IMPACT in order to make recommendations. For each country, we discuss the latest information about hindrances and opportunities to cocoa yield growth, including policies, planned investments and disease status. In almost all the cases, except Indonesia, we recommend adjustments of the IPRs. Alarmingly, none of the countries is projected under baseline scenario assumptions to exceed average yield level of 1 t/ha and half of them is expected to remain below 0.6 t/ha until 2050. This emphasizes the need for a change of the business as usual policies and investments in order to improve the livelihoods of the cocoa growing farmers around the world.